Launching the Israel Journal of Health Policy Research: Why a new journal? Why now? Why open access? - Rosen Bruce; Israeli Avi (BMC, 2012)
Abstract The Israel Journal of Health Policy Research (IJHPR) is a new, open access journal. IJHPR seeks to promote intensive intellectual interactions among scholars and practitioners from Israel and other countries regarding all aspects of health policy, with particular attention to Israel. The ultimate aim of these interactions is to contribute to the development of health policy in Israel, and also to foster wider communication between health scientists and policy analysts in Israel and their colleagues around the world. This inaugural editorial provides an overview of the new journal's rationale and its key features.